Improvable Managerial Skill: Political Skill with its Theoretical and Empirical Aspects - (:unkn) unknown (TURKIYE ORTA DOGU AMME IDARESI ENSTITUSU, 2010)
This study discusses the emergence and structural characteristics of the concept of Political Skill, which has assumed its place in international literature and has developed in the last decade. The study also attempts to explore its reflections on organizations and related processes. The study, which consists of data from international academic articles and books, is based on context analysis. The findings show that political skill has effects on organizations in such a way so as to encompass the employee or leader, himself his peers and inter-organizational groups. Besides, when the conceptual structure is examined, it appears as an improvable skill distinct from dispositional and personal abilities, despite their overlapping aspects. The concept of Political Skill, which is recently being discussed in Turkish literature, is expected to provide academicians and professionals with a new perspective on leadership and management fields.
Keywords: Political skill; skill; leadership; trainable leader; managerial skill; JOB-PERFORMANCE; LEADER REPUTATION; ANTIDOTE; BEHAVIOR; ORGANIZATIONS; STRESSORS